KAJIAN METODE METODE STEGANOGRAFI PADA DOMAIN SPASIAL - Gunawan Wibisono; Tri Waluyo; Erik Iman Heri Ujianto (LPPM Nusa Mandiri, 2020)
This paper contains a review of the spatial domain steganographic literature. The purpose of this paper is to provide knowledge about techniques or methods that exist in the spatial domain of steganography. Steganography is the science or technique for hiding secret messages in other messages so that the existence of the secret message cannot be accessed by others who do not have authority. There are several popular spatial domains of steganographic techniques, namely LSB (Least Significant Bit), which is mapping secret message bits in the rightmost bit (LSB) of each color pixel and PVD (Pixel Value Differencing) which in this method offers a larger message storage capacity , with better image quality compared to other methods in the spatial domain. Because privacy issues continue to develop along with various digital communication technologies, and increasingly strong security threats, steganography can play a role in society to maintain the confidentiality of both picture, voice and video messages. For this reason it is important for us to be aware of steganographic technology and its implications.